Moving towards a palm oil value chain that contributes to the conservation of forests and a reduction in greenhouse gas emissions - Ivanova, Yovita; Tristán Febres, María Claudia; Romero Sánchez, Miguel Antonio; Charry, Andrés; Lema, Sebastián; Choy, José; Vélez Betancourt, Andrés Felipe; Castro Nuñez, Augusto; Quintero, Marcela (International Center for Tropical Agriculture, 2020)
The report "Towards an oil palm chain that contributes to the conservation of forests and the reduction of greenhouse gas emissions: Current status, opportunities with a value chain approach and action plan" presents an input for the development of an environmentally sustainable oil palm chain in the Ucayali region. The document has been produced under the framework of the Sustainable Amazon Businesses (SAB) project, led by CIAT as part of the Bioversity International and CIAT Alliance, in coordination with MINAM and MINAGRI of Peru, and in partnership with the international consulting firm Climate Focus (CF). This project is part of the International Climate Initiative (IKI), supported by the German Federal Ministry for the Environment, Nature Conservation, and Nuclear Safety (BMU). This plan aims to contribute to the effort of the Regional Government of Ucayali (GOREU) to reduce greenhouse gas (GHG) emissions from the agricultural sector, due to the change in land use in the Peruvian Amazon, in accordance with the international commitments of the Peruvian Government for the mitigation of climate change. The document presents an innovative and novel plan to contribute to the environmental sustainability of the oil palm value chain, developed from the perspective of forest conservation and the recovery of degraded ecosystems and with solutions provided by value chain actors. The plan contributes to the Peruvian Government's efforts to comply with the Nationally Determined Contributions (NDC) assumed at the Conference of the Parties - COP21 and the agreement between the Governments of Norway, Germany and Peru - Joint Declaration of Intent (JDI) - two commitments that seek to reduce GHGs. It also seeks to promote the development of national plans, policies and programs with a view to achieving the Sustainable Development Goals (SDA) and Agenda 2030, which recognize that agriculture and climate change cannot be considered separately and therefore require a coherent and integrated approach to sustainability in the agriculture and environment sectors. This report provides information on the oil palm chain that is as up to date as possible, and very useful for the national and regional government, industry, producers, non-governmental organizations and international cooperation agencies, which are currently working towards a chain that will contribute to the sustainable development of agriculture in the Peruvian Amazon. For the development of this document, designed and agreed with key actors in the sector, the project has signed a framework cooperation agreement with the Regional Government of Ucayali (GOREU). Through this cooperation, the articulation of this document with the most relevant development and territorial planning and production instruments of the region has been verified. In addition, the specific elements of this document are expected to contribute to the achievement of the objectives set out in the main management instruments for the Ucayali region and for climate change in the country, including: the Concerted Regional Development Plan (PDRC), the Regional Climate Change Strategy (ERCC) and the Low Emission Rural Development Strategy (ERBE). Based on this report, the SAB project intends to accompany the design and implementation of a pilot business model in the oil palm chain, which will materialize several of the elements of this report, where, in turn, it will take advantage of the emerging financial and market opportunities for products free of deforestation and low in GHG emissions. It is expected that this business model and its subsequent conversion into an investment model can serve for replication and scaling up in the region and in the country; likewise, it will contribute with the references of deforestation-free business models at an international level. Furthermore, it is expected that these models will serve as a basis for the generation of public policies that contribute to the sustainability of the sector.